Feasibility of a multidisciplinary Transitional Pain Service in spine surgery patients to minimise opioid use and improve perioperative outcomes: a quality improvement study - Sarah Tierney; Patricia Poulin; Daniel McIsaac; Marie-Claude Magnan; Amin Zahrai; Alexandra Stratton (BMJ Open Quality)
Introduction Spine surgery patients have high rates of perioperative opioid consumption, with a chronic opioid use prevalence of 20%. A proposed solution is the implementation of a Transitional Pain Service (TPS), which provides patient-tailored multidisciplinary care. Its feasibility has not been demonstrated in spine surgery. The main objective of this study was to evaluate the feasibility of a TPS programme in patients undergoing spine surgery.Methods Patients were recruited between July 2020 and November 2021 at a single, tertiary care academic centre. Success of our study was defined as: (1) enrolment: ability to enrol ≥80% of eligible patients, (2) data collection: ability to collect data for ≥80% of participants, including effectiveness measures (oral morphine equivalent (OME) and Visual Analogue Scale (VAS)-perceived analgesic management and overall health) and programme resource requirements measures (appointment attendance, 60-day return to emergency and length of stay), and (3) efficacy: estimate potential programme effectiveness defined as ≥80% of patients weaned back to their intake OME requirements at programme discharge.Results Thirty out of 36 (83.3%) eligible patients were enrolled and 26 completed the TPS programme. The main programme outcomes and resource measures were successfully tracked for >80% of patients. All 26 patients had the same or lower OME at programme discharge than at intake (intake 38.75 mg vs discharge 12.50 mg; p<0.001). At TPS discharge, patients reported similar overall health VAS (pre 60.0 vs post 70.0; p=0.14), improved scores for VAS-perceived analgesic management (pre 47.6 vs post 75.6; p<0.001) and improved Brief Pain Inventory pain intensity (pre 39.1 vs post 25.0; p=0.02).Conclusion Our feasibility study successfully met or exceeded our three main objectives. Based on this success and the defined clinical need for a TPS programme, we plan to expand our TPS care model to include other surgical procedures at our centre.